Teaching EFL Students Using Selected Media: Offline Video Taken From YouTube - Rohandi Yusuf (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2020)
English is a foreign language that must be studied, there are four skills that students must master, namely writing, speaking, reading and pronunciation. The development of technology in the learning process of teachers is required to use media not only using books, markers, or other things that are not related to technology that will make teachers or students miss technological development. The current era of globalization is a lot of media or tools for teaching teachers, namely using smartphones, laptops, one of them is a website, application, social media such as Facebook, Instagram, Twitter, Line or other social media, and the last is YouTube. In this study we use YouTube offline video as a teaching media process. Using the media in the learning process and YouTube include new media or ways in the learning process and using YouTube definitely brings impact. Of course a positive impact for students or teachers in the learning process. This study will tell so much about the use of YouTube as a medium for teacher learning in learning English.